Evaluating the effects of wildfire in piñon-juniper woodlands on bighorn sheep habitat and vegetation composition - Wilson, Benjamin R., author; Boone, Randall, advisor; Evangelista, Paul, committee member; Wittemyer, George, committee member (Colorado State University. Libraries, 2014)
I evaluated the efficacy of using woodland fire to alter vegetation composition in a manner that augments desert bighorn sheep (Ovis canadensis nelsoni) habitat in the Black Ridge Canyons Wilderness Area in western Colorado. I applied generalized linear mixed models to estimate pre-fire ewe habitat selection and then simulated a hypothetical widespread fire to spatially predict where fire would be most beneficial in expanding habitat. I found that ewes were avoiding habitats with high woodland canopy cover, the habitat most likely to be removed by fire. Given the removal of all woodlands, it is likely that habitat expansion would occur in areas near topographic escape terrain. Coupled with this analysis, I addressed concerns regarding potential negative effects of fire in this system by comparing vegetation composition of unburned habitats to burned habitats that were treated with a native seed mixture. I found that foliar cover in burned areas was on average two times greater than in unburned areas and that post-fire seeding efforts likely allowed for these differences to be proportionally similar between native and non-native grass species. My results provide an encompassing view on the effects of fire for a common management situation in which both land and wildlife values are of mutual interest.